2010
DOI: 10.1039/b923029g
|View full text |Cite
|
Sign up to set email alerts
|

Thymidine-functionalized silica nanotubes for selective recognition and separation of oligoadenosines

Abstract: Thymidine receptor residues were covalently attached to the inner side wall of silica nanotubes (SNTs). The adsorption capacities of the thymidine-functionalized silica nanotubes (T-SNTs) with nucleic acids and oligonucleic acids were evaluated. The T-SNTs exhibited excellent selectivity both in recognition and separation of adenosine and adenosine-based oligonucleotides, because adenosine and oligoadenosine were selectively bound to the inner surface of T-SNTs by formation of complementary intermolecular hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…So far, several enzymes, such as lysozyme [57], penicillin G acylase [58], or glucose oxidase [59] have been immobilized on silica nanotubes, as well as fluorescent laser dyes [60] or thymidine for adenosines separation [61]. To demonstrate the versatility of the newly synthesized organosilica-nanotubes, the amino acid glycine was grafted on ethylenesilica-nanotubes.…”
Section: Grafting Of Glycine On Esntmentioning
confidence: 99%
“…So far, several enzymes, such as lysozyme [57], penicillin G acylase [58], or glucose oxidase [59] have been immobilized on silica nanotubes, as well as fluorescent laser dyes [60] or thymidine for adenosines separation [61]. To demonstrate the versatility of the newly synthesized organosilica-nanotubes, the amino acid glycine was grafted on ethylenesilica-nanotubes.…”
Section: Grafting Of Glycine On Esntmentioning
confidence: 99%
“…In particular, silica nanotubes (SNTs) arouse special interest because they are biocompatible, photoluminescent, and their surfaces are accessible and can be modified [14]. It is reported that SNTs have extensive applications in organic molecular separation, decomposition of pollutants and inorganic ion sensors, etc [15][16][17][18]. As novel tubular materials, silica nanotubes have good mechanical properties to resist the outer impact and pull forces, possessing the advantages of both functional materials and structural materials.…”
Section: Introductionmentioning
confidence: 99%
“…Nano-silica fabricated with AgNPs has been reported as an efficient adsorbent for the dye contaminants in water[63]. Similarly, pure and Ag-doped SiO 2 present reliable property in the adsorption of chlorinated compounds in water[64].Jung et al[65] attached thymidine receptor residues to the inner side wall of silica nanotubes (SNTs) covalently. The composite material T-SNTs exhibited excellent selectivity both in recognition and separation of adenosine and adenosine-based oligonucleotides through the formation of complementary intermolecular hydrogen bonds.…”
mentioning
confidence: 99%